Craving among Synthetic Cannabinoid Users: A Qualitative Approach - Dalgıç, Yağmur Suadiye; Coşkunol, Hakan (Addicta: The Turkish Journal on Addictions, 2021)
Synthetic cannabinoids are accepted as new-design substances with strong addictive properties. The development of addiction in users is linked to craving. Persistent craving, which is defined as a strong subjective urge to use drugs, is a key clinical symptom criterion for addiction-related disorders in the Diagnostic and Statistical Manual of Mental Disorders-5. This study explores the craving experiences of synthetic cannabinoid users. Therefore, elaboration of craving experiences of synthetic cannabinoid users will contribute to a better understanding of it and to the development of new treatment strategies. The research was designed as an interpretive phenomenological analysis to investigate the craving phenomenon in depth. Face-to-face interviews were carried out using semi-structured interview forms developed by the researcher. The data were collected from 11 participants who were users of the synthetic cannabinoids known as Bonsai and Jamaica in Turkey. The findings revealed that craving is an experience that has emotional, behavioral, and cognitive dimensions for synthetic cannabinoid users. The results also showed that craving is expressed as “want.” This want is uncontrollable and has the purpose of obtaining pleasure. The act of smoking the substance can continue automatically. Its addictive effects such as relaxation, pleasure, happiness, and relieving troubles can be imagined and experienced visually by the users.